Marketing management of medical organization - ZRYBNIEVA, IRYNA; Zavolichna, Tetyana (High School of Economics and Management (Bratislava, Slovakia), Higher School of Medicine (Poland, Sosnowiec), Higher State Educational Establishment of Ukraine “Bukovinian State Medical University” (Chernivtsi, Ukraine), 2018)
Marketing management of a medical organization is a modern tool for improving the system of work with personnel, which coordinates the interaction of three subsystems of management: marketing, general management and quality management of medical services. The marketing of medical services is intended to identify the needs of the population in health services, identify the best ways to meet them in the process of competitive struggle for the consumer in order to achieve the main goals. The main objectives are realized through intermediate ones, for example, for the line of goods and quality of services, pricing methods, places and methods of their sale, systems of promotion, staff contacting with customers.
Keywords: Marketing; management; medical organization